1997
DOI: 10.1258/0956462971919543
|View full text |Cite
|
Sign up to set email alerts
|

Pilot studies of azithromycin, letrazuril and paromomycin in the treatment of cryptosporidiosis

Abstract: Pilot studies of the safety and efficacy of 3 drugs thought to have anticryptosporidial activity were carried out to determine whether any of them are suitable for large-scale clinical trials. Open studies of the use of azithromycin, letrazuril and paromomycin in patients with acquired immunodeficiency syndrome (AIDS) and confirmed cryptosporidial diarrhoea for at least a month. Azithromycin 500 mg daily was ineffective. Letrazuril 150-200 mg daily was associated with an improvement in symptoms in 40% of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…Some success has been reported with pyrimethamine and trimethoprim-sulfamethoxazole in patients infected with Isospora belli, another opportunistic intestinal parasite whose clinical effects include severe and unremitting diarrhea and thus resemble those produced by C. parvum (12,77). Several other experimental treatments using non-antifolate drugs have also been reported, some of which are likely to act primarily on the host cell rather than the parasite (1,5,6,32,34,37,42,43,47,78). The efficacy of these regimens is, at best, marginal.…”
mentioning
confidence: 99%
“…Some success has been reported with pyrimethamine and trimethoprim-sulfamethoxazole in patients infected with Isospora belli, another opportunistic intestinal parasite whose clinical effects include severe and unremitting diarrhea and thus resemble those produced by C. parvum (12,77). Several other experimental treatments using non-antifolate drugs have also been reported, some of which are likely to act primarily on the host cell rather than the parasite (1,5,6,32,34,37,42,43,47,78). The efficacy of these regimens is, at best, marginal.…”
mentioning
confidence: 99%
“…In a pilot study in Egyptian schoolchildren, treatment with 500 mg/day for 3 weeks resulted in a 91% cure rate and a 99% reduction in oocysts in stool samples [34]. By contrast, Blanshard and colleagues noted that the frequency of resolution of diarrhea in patients treated with azithromycin was similar to the spontaneous remission rate reported in AIDS patients with cryptosporidiosis [25]. A large multicenter study, reported as an abstract, noted no difference in oocyst shedding, stool frequency and weight loss between patients who were treated with azithromycin (900 mg orally daily) or placebo control [24].…”
Section: Azithromycinmentioning
confidence: 91%
“…Paromomycin has been used for the treatment of cryptosporidiosis in adults and children with various levels of success [23,24]. A number of Editorial Treatment of cryptosporidiosis uncontrolled trials and case reports described clinical improvement of AIDS patients with cryptosporidiosis after treatment with paromomycin [23,25]. However, organisms were seldom eliminated from stools, and relapse of diarrhea occurred in over half of the patients.…”
Section: Paromomycinmentioning
confidence: 99%
“…Letrazuril, a derivative of diclazuril, showed promise in a pilot study. At a dosage of 150-200 mg daily, letrazuril was associated with an improvement in symptoms in 40 % of patients treated and cessation of excretion of cryptosporidial oocysts in the stool in 70 % (Blanshard et al 1997). However, biopsies from these patients remained positive.…”
Section: Benzeneacetonitrile Antibioticsmentioning
confidence: 97%
“…Azithromycin treatment resulted in symptomatic relief in immunosuppressed children and in patients with chronic cryptosporidiosis (Russell et al 1998;Vargas et al 1993). When given at a dose of 500 mg daily to patients with AIDS it was reported to be both effective (Kadappu et al 2002) or ineffective (Blanshard et al 1997). Extraintestinal infections (respiratory) in immunocompromised (HIV) patients responded positively to azithromycin alone or in combination with paromomycin (Palmieri et al 2005;Tali et al 2011).…”
Section: Macrolide Antibioticsmentioning
confidence: 99%